Can Amputation Save the Hospital? The Impact of the Medicare Rural Flexibility Program on Demand and Welfare - Philipp Schmidt-Dengler; Gautam Gowrisankaran; Claudio Lucarelli; Robert Town (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper seeks to understand the impact of the Medicare Rural Hospital Flexi- bility (Flex) Program on rural resident hospital choice and welfare. The Flex program created a new class of hospital, the Critical Access Hospital (CAH), which receives more generous reimbursement in return for limits on capacity and length of stay. We fi nd that conversion to CAH status reduced inpatient admissions by a mean of 5.4%, of which almost all was driven by factors other than capacity. The program increased consumer welfare if it reduced the closure rate by at least 4 percentage points.
Keywords: D12; I18; I11; 330